Integration of Fingerprinting Codes for Image Watermarking Application - Hasan Nasir Shaik (2014)
Watermarking is an accepted phenomenon to discourage illegal distribution of multimedia. Using a traitor tracing scheme such as Transaction Watermarking one is able to trace a distributed copy back to the responsible. However, this is no longer true if several customers of the same content collaborate and conduct a so called collusion attack. Collusion attacks aim to manipulate the Transaction Watermark Messages. Common theoretical approaches to counter such attacks are mathematical Fingerprinting Codes which usually require long code length corresponding large embedding payload. Thus, a huge challenge is to apply these schemes for image watermarking. Since images only have limited embedding payload, it is hard to successfully embed a Fingerprinting Code consisting of thousands of bits. The goal of this thesis is to explore which theoretical schemes are appropriate for embedding, and to integrate the most applicable one into a current image watermarking application, maintaining the quality of the image and properties of the watermark.